The COMPOND COMPOSITION OF AIRLESS TIRE TREAD (AIRLES TYRE) - Kurniawan, Hamzah; Saefullah, Lalu; Hidayat, Muhammad Iman (Jurnal Otoranpur, 2021)
The tire without air is a tire that has a very extraordinary influence on the units of vehicle users, both public vehicles and tactical vehicles in the military. In addition to being used in the field of duty, this airless tire can be used for other supporting vehicles of army so there are not many obstacles during operations. Therefore, it takes good materials and proper calculations in making this airless tire tread so that in the future there are no obstacles when using it. The research methods used are experimental methods and field studies. The study was conducted repeatedly and the data was taken directly in the field. After mechanical testing of the rubber material is done to find out the physical properties of the strength of the material. Furthermore, the entire printing and assembly process is carried out and tested on the vehicle, for the conclusion of static analysis of rubber sample material that has been done has determined the proper hardness for the material connected with polyurethane, the appropriate hardness for this rubber is 80 KN/mm. The process has been tested from each sample of rubber hardness variations and the results are determined, in addition to rheometer testing or maturation process takes 5 minutes and is given a temperature of 100 °C and is assisted by hydraulic so that air from volcanic rubber is lost with the help of hydraulic pressure.